2014
DOI: 10.4014/jmb.1307.07081
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of Acidic Diacetate Sophorolipid as Biostabilizer for ZnO Nanoparticle Synthesis and Biofunctionalizing Agent Against Salmonella enterica and Candida albicans

Abstract: In the present study, a yeast species isolated from CETP, Vellore, Tamilnadu was identified as Cryptococcus sp. VITGBN2 based on molecular techniques and was found to be a potent producer of acidic diacetate sophorolipid in mineral salt media containing vegetable oil as additional carbon source. The chemical structure of the purified biosurfactant was identified as acidic diacetate sophorolipid through GC-MS analysis. This sophorolipid was used as a stabilizer for synthesis of zinc oxide nanoparticles (ZON). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 19 publications
(21 reference statements)
3
26
0
Order By: Relevance
“…Microbicidal activity of NiGs is also due to the electrostatic interaction between positively charged nickel ions and negatively charged microbial cell membranes. These observations are in concurrence with earlier antimicrobial study [16] of zinc oxide nanoparticles against S. enterica and C. albicans.…”
Section: Growth Curves Of Microbial Cells Treated With Different Concsupporting
confidence: 92%
See 1 more Smart Citation
“…Microbicidal activity of NiGs is also due to the electrostatic interaction between positively charged nickel ions and negatively charged microbial cell membranes. These observations are in concurrence with earlier antimicrobial study [16] of zinc oxide nanoparticles against S. enterica and C. albicans.…”
Section: Growth Curves Of Microbial Cells Treated With Different Concsupporting
confidence: 92%
“…After incubation, the contents were centrifuged at 5000 rpm for 5 min and supernatant was collected. 200 L of supernatant from each sample was mixed with 800 L of Bradford reagent and incubated for 10 min in dark at 37 ∘ C. The optical density was determined at 595 nm with bovine serum albumin as standard [16].…”
Section: Detection Of Reactive Oxygen Species (Ros)mentioning
confidence: 99%
“…Furthermore, Basak et al . () reported that SL‐capped ZnO nanoparticle‐mediated C. albicans cell death occurs via membrane bursting followed by oozing out of proteins and intracellular materials. In addition to functioning as a cyclic lipopetide, the biosurfactant, SUR, has been found to exhibit versatile bioactive features including adjuvant for immunization and antitumour properties.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Nanoparticle-based therapeutics have been considered as some of the most promising platforms in drug delivery applications due to their ability to increase drug accumulation in solid tumours by enhanced permeability and retention (EPR) and MDR reversal through bypassing or inhibiting P-gp activity (Bao et al 2016). Furthermore, Basak et al (2014) reported that SL-capped ZnO nanoparticle-mediated C. albicans cell death occurs via membrane bursting followed by oozing out of proteins and intracellular materials. In addition to functioning as a cyclic lipopetide, the biosurfactant, SUR, has been found to exhibit versatile bioactive features including adjuvant for immunization and antitumour properties.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…In the present study, the smaller size of NiO nanoparticles was thought to be responsible for better antibacterial actions than its bulk form, as smaller size usually enhancedby the dispersibility and penetration into the intracellular matrix and interference with intracellular Ca 2+ absorption leading to cell damage [22]. Attachment of the nickel ions released from the NiO nanoparticles to the cell membrane of the microbes initiate electrostatic interactions, wherein it interferes with cellular physiology leading to their disruption [34]. Further, these damaged cell membranes are more susceptible to further interactions, which lead to more penetration of NiO nanoparticles and leakage of the intracellular organelles [22].…”
Section: Resultsmentioning
confidence: 78%